Arriving Safely: Decreasing Rapid Escalations in Care for Incoming Transported Pediatric Patients. Issue 1 (27th January 2023) - Zheng, Christie; Gibson, Cynthia; Jeong, Hyungjoo; Port, Courtney
Abstract : Introduction: Accurate inpatient placement at the level of care needed for incoming transported patients can present challenges that may result in a rapid escalation in care following admission to the general inpatient unit. The Pediatric Early Warning System (PEWS) score is useful for early recognition of clinical deterioration. Therefore, we aimed to reduce rapid escalations in care for incoming transported patients via the implementation of an escalation algorithm with a goal of 80% PEWS score completion rate during transport within 6 months. Methods: We created an escalation algorithm utilizing PEWS scores and direct lines of communication between emergency medical technicians and receiving physicians. Audit and feedback increased the adoption of the process. We defined rapid escalations as transfer to a higher level of care within 6 hours of admission. Results: PEWS score completion increased from a mean of 48% to 70%. This result varied by emergency medical technician crew level of care. Eleven percent (n = 114) of PEWS scores required physician notification, 20% (n = 23) of which resulted in interventions en route. There were no differences in rapid escalation rates over time, but it remained low at <2% of all incoming transported patients. Some crew members report improved communication with hospital providers and feel more empowered to speak up when a patient's assessment is not as expected following algorithm implementation. Conclusions: This project improved PEWS score completion and maintained a low rate of rapid escalations of care among incoming transfers.